Comprehensive Analysis of the Main Agronomic Traits of Different Varieties (Lines) of Jute - Xingcai An; Xiahong Luo; Xia An; Changli Chen; Tingting Liu; Lina Zou; Shaocui Li (Journal of Natural Fibers)
To investigate the genetic diversity of jute germplasm resources across different varieties (lines) and enhance the efficiency of comprehensive utilization of jute germplasm resources, this study employed a randomized block design to examine and analyze various agronomic traits of 15 jute varieties (lines) collected and to determine the fiber strength.The results demonstrated that the coefficients of variation for 22 agronomic traits across 15 varieties varied between 6.48% and 56.82%. The highest coefficient of variation was recorded for breaking work, followed closely by the number of branches, while the sun-drying rate of fresh bones exhibited the lowest coefficient. Principal component analysis indicated that the cumulative contribution rate of the first six principal components reached 90.98%. Additionally, affiliation function analysis revealed that “Mowei 1” demonstrated the highest affiliation function value, closely followed by “83–1” and “Jute 179.” This suggests that these varieties possess superior overall performance and significant potential for further development and utilization. This study provides a scientific basis for the selection, preservation and popularization of jute germplasm resources in China.